Stena - Rakoyed, Alexander (Ukraine, 2014)
The film documents the problems that were surrounded by the Berlin wall in Germany. This is when crossing the road can cost you your life, this is when you are not allowed to see your relatives living in the next block for almost thirty years, and this was 150 kilometers of concrete and barbed wire tearing the city, country and the world into pieces.
Verzio Film Festival Submission
Keywords: Documentary films